Love, a way of glossa: on digging the land of the bodies and the languages - Almeida, Gil Roberto; Lignelli (Universidade de Brasília ‒ UnB, Brasília/DF, Brazil), César (Revista Brasileira de Estudos da Presença, 2022)
The act of digging, as pictured in a Paul Celan’s poem, figures as the starting point to evoke the potential of love as a poetic act able to form new affects and political subjects. Such notion about love, contrary to the romantic tradition, leads to a tension between the individual borders and all that makes him a person, in the perspective of a criticism of the humanist perception and of the theological-political project of the neoliberal capital. For this provocative intent, the ideas of some authors, as Nietzsche, Deleuze, Derrida and Safatle, reverberate here. It is a kind of digging that, as the loving act itself, heads to an ethical and aesthetic exercise involving the languages and bodies’ stratum as a way of making escape other potentialities swashing a policy of the inhumane.